A Quantitative Investigation: Applying the 4P’s of Marketing to Entrepreneurial Accounting and Tax Preparer Firms - Putulowski, Joe; Ardito, Rick; Crosby, Robert (Technium Social Sciences Journal, 2021)
Each year thousands of aspiring entrepreneurs begin the purist of a dream by starting their own business. However, more than half of the new startup business establishments will not make it to their first anniversary (U.S. Small Business Administration, 2016). This extraordinary high failure rate puts a tremendous burden on the entrepreneur, stakeholders, stockholders, and local communities. The purpose of this study was to utilize research to form a better understanding of how potential customers perceived tax and accounting services, the professionals that provide them, and their attitudes towards utilizing technology to deliver those services. Participants were 178 online college students (35.4% men, 64.6% women) ages 18 to 56 (M = 30.8, SD = 8.72) attending a midsized private Christian university in Southern California. Results provide support for entrepreneurs to adopt, in part, a differentiation strategy to effectively promote their firm, brand, and message. Keywords: Marketing, 4P’s, Marketing mix, quantitative research, entrepreneur, accounting, tax preparation services